Contributions of international sources to PM2.5 in South Korea. (15th September 2021) - Kumar, Naresh; Park, Rokjin J.; Jeong, Jaein I.; Woo, Jung-Hun; Kim, Younha; Johnson, Jeremiah; Yarwood, Greg; Kang, Suji; Chun, Sungnam; Knipping, Eladio
Abstract: The air quality in Republic of Korea, especially in cities such as Seoul, has been a serious public health concern over the years. The key pollutant in the atmosphere leading to poor air quality in Korea is fine particulate matter (PM2.5 ). Here, we use a 3-D global chemistry model (GEOS-Chem) to conduct source attribution to PM2.5 in Korea from international and domestic emissions. The modeling was done for 2015 and 2016 to account for different meteorological conditions. We ran the GEOS-Chem model for both years, conducted model evaluation using ground and aloft observations, and then conducted sensitivity simulations without domestic anthropogenic emissions and Chinese anthropogenic emissions, respectively. Results show that the Chinese influence on PM2.5 in Korea varies from month to month with the highest contribution during spring when observed concentrations are also the highest. Chinese contributions to PM2.5 concentrations in South Korea reach a maximum of up to 60% in January and February and gradually decrease until August when they reach a minimum at about 20%. On an annual basis, our analysis estimated that in 2016, Chinese anthropogenic emissions contributed 45% to PM2.5 in South Korea. The 2016 contribution from China was generally 3–5% lower than in 2015 because of emissions reductions in China. Compared to the Chinese contribution, the rest of the world contributions (which also include contributions from natural emissions worldwide) were minor except for summer in the South Sea. Highlights: A global model estimated Chinese and domestic contributions to PM2.5 in Korea. Influence from China on PM2.5 in Korea was the highest during winter and spring. Contributions from China were 60% in January/February and 20% in August. Domestic contributions were also the highest during winter months.